Beneficial effects of anti-EGFR agents, Cetuximab or Nimotuzumab, in combination with concurrent chemoradiotherapy in advanced nasopharyngeal carcinoma. (May 2018) - Lin, Mei; You, Rui; Liu, You-Ping; Zhang, Yi-Nuan; Zhang, Hao-Jiong; Zou, Xiong; Yang, Qi; Li, Chao-Feng; Hua, Yi-Jun; Yu, Tao; Cao, Jing-Yu; Li, Ji-Bin; et al.
Highlights: The combination of anti-EGFR agents (CTX/NTZ) with concurrent chemoradiotherapy (CCRT) is comparable to induction chemotherapy (IC) plus CCRT treatment in survival outcomes for locoregionally advanced NPC patients. Patients undergoing IC plus CCRT suffered from severe hematologic toxicity and diarrhea compared with those treated with CTX/NTZ plus CCRT. The addition of CTX/NTZ to CCRT is an effective and safe alternative treatment strategy for locoregionally advanced NPC patients. Abstract: Objective: This study aimed to evaluate the efficacy and safety in locoregionally advanced nasopharyngeal carcinoma (NPC) patients receiving concurrent chemoradiotherapy (CCRT) plus Cetuximab (CTX) or Nimotuzumab (NTZ) compared to those receiving induction chemotherapy (IC) plus CCRT. Materials and methods: From January 2008 to December 2013, 715 eligible patients were enrolled in the study. Using propensity scores to adjust for gender, age, Karnofsky performance status (KPS), tumor stage, node stage, and clinical stage, a well-balanced cohort was created by matching each patient who received CTX/NTZ plus CCRT (137 patients) with two patients who underwent IC plus CCRT (274 patients). The primary endpoint was overall survival (OS), and other outcome variables included disease-free survival (DFS), distant metastasis-free survival (DMFS) and loco-regional relapse-free survival (LRRFS). Results and conclusion: The median follow-up was 57.0 months and 55.0 months for the CTX/NTZ plus CCRT group and IC plus CCRT group, respectively. No significant differences were found between the CTX/NTZ plus CCRT group and the IC plus CCRT group in 3-year OS (95.5% vs. 94.7%, P = 0.083), 3-year DFS (93.3% vs. 86.1%, P = 0.104), 3-year DMFS (96.2% vs. 92.5%, P = 0.243) and 3-year LRRFS (97.0% vs. 95.1%, P = 0.297). Patients undergoing IC plus CCRT suffered from severe hematologic toxicity and diarrhea compared with those treated with CTX/NTZ plus CCRT. The combination of CTX/NTZ with CCRT is comparable to IC plus CCRT treatment in survival outcomes for locoregionally advanced NPC patients but has a better safety profile than IC plus CCRT treatment.